DESAIN STUDENT WORKSHEET MATEMATIKA BERBASIS DISCOVERY LEARNING NUANSA ETNOMATEMATIKA SAM POO KONG - Evril, Chintia; Dian Mawarsari, Venissa; Joko Suprayitno, Iswahyudi (Jurnal Citra Pendidikan, 2025)
Mathematical communication is one of the important skills in mathematics learning. Based on observations at Kebon Dalem Junior High School Semarang, the limited mathematical communication of students is caused by the unavailability of appropriate learning media. This research aims to design a student mathematics worksheet based on discovery learning with the nuances of Sam Poo Kong's ethnomathematics in which there is a strengthening of students' mathematical communication skills. This research uses the Research and Development (R&D) method with the ADDIE development model which focuses on the first three stages, namely Analyze, Design, and Develop. The research instrument was in the form of a validation questionnaire assessed by three validators, consisting of two lecturers and one teacher, to assess the feasibility aspects of content, language, approach, Sam Poo Kong's ethnomathematics, mathematical communication, and media. The validation results showed that the student worksheet developed obtained an average score of 90% from material experts and media experts, which is classified as very valid. Thus, this discovery learning-based student worksheet with Sam Poo Kong's ethnomathematical nuances is suitable for use as a learning medium.